Urgensi Plea Bargaining System Dalam Pembaruan Sistem Peradilan Pidana Di Indonesia: Studi Perbandingan Plea Bargaining System Di Amerika Serikat - Ruchoyah Ruchoyah (Fakultas Hukum Universitas Islam Indonesia, 2020)
This study aims to answer two problems: first, how is the concept of implementing a bargaining system in the criminal justice system in the United States? Second, what is the urgency of implementing the Plea Bargaining System in reforming the criminal justice system in Indonesia. The research method used is juridical normative with a conceptual approach and comparison method. This paper intends to provide legal problem solving for the accumulation of criminal cases in Indonesia, namely by implementing a plea bargaining system in reforming the criminal justice system in Indonesia. This study concludes that, first, In the United States, the plea bargaining mechanism is carried out at the arraignment and preliminary hearing stages. Second, the plea bargaining system in the United States is regulated in the Federal Rules of Criminal Procedure rule 11. The urgency of implementing a plea bargaining system in the criminal justice system in Indonesia can be seen from several considerations, namely philosophical, juridical, sociological, and political-legal considerations. The conclusions and recommendations of the authors are implementing a plea bargaining system in reforming the criminal justice system in Indonesia in order to realize an effective and efficient criminal justice.